2007
DOI: 10.1002/cta.451
|View full text |Cite
|
Sign up to set email alerts
|

On global exponential stability of standard and full‐range CNNs

Abstract: SUMMARYThis paper compares the dynamical behaviour of the standard (S) cellular neural networks (CNNs) and the full-range (FR) CNNs, when the two CNN models are characterized by the same set of parameters (interconnections and inputs). The FR-CNNs are assumed to be characterized by ideal hard-limiter nonlinearities with two vertical segments in the i-v characteristic. The main result is that some basic conditions ensuring global exponential stability (GES) of the unique equilibrium point of S-CNNs, with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Among them, identical synchronization of coupled complex networks has attracted more attention, since 632 X. LIU AND T. CHEN synchronization can not only explain many natural phenomena [7], but also have many applications, such as neural networks, image processing, secure communication, etc., see [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among them, identical synchronization of coupled complex networks has attracted more attention, since 632 X. LIU AND T. CHEN synchronization can not only explain many natural phenomena [7], but also have many applications, such as neural networks, image processing, secure communication, etc., see [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, an increasing interest has been devoted to the study of complex networks, see [1][2][3][4][5][6], which can be regarded as a composition and interaction of several dynamical nodes. Among them, identical synchronization of coupled complex networks has attracted more attention, since 632 X. LIU AND T. CHEN synchronization can not only explain many natural phenomena [7], but also have many applications, such as neural networks, image processing, secure communication, etc., see [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we allow for the presence of a concentrated delay (D) in the neuron interconnections. The D-FRCNNs, introduced in [9], are expected to have advantages over delayed SCNNs analogous to those obtainable with FRCNNs. We also stress that the presence of delays is important in view of applications typical of the CNN paradigm to the solution of motion related problems in real time.…”
Section: Introductionmentioning
confidence: 98%
“…Results obtained so far along this line fall in two groups. On one hand it has been shown that there are classes of neuron interconnection matrices, such as symmetrizable matrices, matrices with non-negative off-diagonal entries [7] and Lyapunov Diagonally Stable matrices [8] for which the qualitative behavior of the solutions of FRCNNs is indeed analogous to that of the SCNNs for the same set of parameters. On the other hand, there are also cases where the global dynamical behavior of FRCNNs is basically different from that of SCNNs with the same set of parameters.…”
Section: Introductionmentioning
confidence: 99%